Perceptions of ESL students about using web-concordancing and language reference resources in academic writing - Abd Samad, Arshad; Shakibkotamjani, Sedigheh; Mohamed Razali, Abu Bakar; Heidari, Marjan; Panah, Ebrahim (Conscientia Beam, 2020)
Online corpora as valuable resources have received considerable attention in teaching English for academic purposes (EAP). The current study investigated ESL participants’ perception of using online concordancers and other reference resources in their academic writing outside the classroom context, after some initial hands-on practice in the classroom. The researcher designed an online interface and included multiple reference resources such as concordancers, thesaurus, online dictionaries and Google as the main search engine. This study used a qualitative case study approach through conducting semi-structured interviews and stimulated recall to achieve in-depth descriptions of the participants’ perceptions of corpus consultation. The findings revealed that the process of corpus consultation is time-consuming; however, the multiple resources assisted the participants to experience new ways of encoding their intended meanings. They became more attentive to the accuracy and appropriacy of the language they use to convey their intended meaning. It was found that not only did reference resource consultation raise participants’ awareness of the lexico-grammatical aspects, but also increased their confidence in academic writing.